No todo lo que brilla es oro: apariencia del derecho y protección de los terceros de buena fe - O’Neill de la Fuente, Cecilia (2016)
What happens to the third party that, in good faith, acquires rights from a subject whose title is not valid? With few exceptions, the Peruvian Civil Code leaves him unprotected. In this article, the author evaluates the specific solutions contained in the Peruvian Civil Code; analyzes the answers that foreign legislations present; and, finally, proposes a solution to protect the third parties in good faith who acquire rights from an apparent owner.